MENINGKATKAN MOTORIK HALUS ANAK MELALUI BERMAIN PLASTISIN DI TAMAN KANAK-KANAK PERTIWI DOMPYONG - Asriani Asriani; Tri Setyaningsih (TEMATIK: Jurnal Pemikiran dan Penelitian Pendidikan Anak Usia Dini, 2021)
Early childhood education is one of the educational institutions that play an important role to help the government prepare the younger generation as early as possible which is the goal of early childhood education which helps lay the foundation for the development of behavioral attitudes, knowledge, skills, and creativity needed by students. This study aimed to find out the Improvement of Children's Fine Motor Skills Through Plasticine Play in Dompyong Kindergarten. They were the subject of 15 children. Data is collected using observation sheets. The data is analyzed using descriptive analysis. Based on the results of observations in the study, it can be concluded that playing plasticine by following the learning steps established can improve students' fine motor. This improvement is seen in indicators 1) Coordination of the child's hands and eyes in composing plasticine, 2) Smoothness of the child's arm in making a shape from plasticine material. The increase is seen in the results of the average value of the cycle of 2 students for two indicators is 3.60, and the complete value of learning is 100%